A functional variant of the neuropeptide S receptor‐1 gene modulates clinical outcomes and healthcare utilization in patients with systolic heart failure: results from the Interdisciplinary Network Heart Failure (INH) Study. (18th December 2016) - Angermann, Christiane E.; Kaspar, Mathias; Marx, Almuth; Kittel‐Schneider, Sarah; Menhofer, Dominik; Störk, Stefan; Ertl, Georg; Domschke, Katharina; Deckert, Jürgen; Reif, Andreas
Abstract : Aims: Psychopathologies may occur in heart failure (HF) and can be associated with adverse outcomes. Amongst neuropeptide S receptor gene functional sequence variants, the T‐allele [asparagine(107)isoleucine, NPSR1 rs324981] has been identified as a risk factor for increased anxiety/overinterpretation of bodily symptoms. We investigated all‐cause death and re‐hospitalization (composite primary endpoint, CPEP) and healthcare utilization in patients hospitalized for decompensated systolic HF with the TT vs. the AT/AA genotype. Methods and results: Participants in the Interdisciplinary Network Heart Failure programme were eligible if consenting to genetic testing ( n = 924) and randomization to usual care (UC, n = 464) or nurse‐co‐ordinated disease management (DM, n = 460). Follow‐up was 180 days (100% complete). Compared with AT/AA carriers ( n = 726), TT genotype carriers ( n = 198) had more CPEP events [47% vs. 39%, hazard ratio (HR) 1.27, 95% confidence interval (CI) 1.01–1.61, P = 0.044] and were more frequently re‐hospitalized (43% vs. 35%, HR 1.31, 95% CI 1.02–1.67, P = 0.033); mortality rate was similar in both groups (HR 1.11, 95% CI 0.68–1.81, P = 0.664). In subjects undergoing DM, CPEP and re‐hospitalization occurred more often in TT (51% and 47%) than in AT/AA carriers (36% and 33%; HR 2.14, 95% CI 1.44–3.19, and HR 2.29, 95% CI 1.52–3.44, genotype/treatment interaction both P = 0.007). Furthermore, TT genotype carriers undergoing DM visited cardiologists and other specialists more often than AT/AA carriers ( P = 0.009 and P = 0.005). With UC, event rates did not differ between genotype subgroups. Conclusion: We identified a psychogenetic determinant of clinical outcomes and healthcare utilization after acute HF, which was modulated by the type of care. Future investigations need to clarify whether NPSR1 genotyping might further enhance the concept of 'personalized' medicine in HF. Trial registration: ISRCTN23325295.